Poverty Level Analysis in South Sulawesi Province - Herman; Rahmatia; Abdireviane, Indraswati Tri (PT. Maju Malaqbi Makkarana, 2023)
This study aims (1) to analyze the effect of population on poverty. (2) To analyze the effect of unemployment on poverty. (3) To analyze the effect of education on poverty This research is quantitative using multiple linear regression analysis with time series data. Namely the factors that influence the level of poverty in South Sulawesi. The results of the study explain that the population has a negative and significant effect on the level of poverty, education simultaneously has a negative and significant effect on poverty in South Sulawesi, on the other hand the unemployment rate has a negative but not significant effect on poverty in South Sulawesi.